TEACHING KARAKALPAK LANGUAGE IN SCHOOLS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article deals with the issues of teaching the Karakalpak language in educational institutions where education is conducted in other (foreign) languages, as well as the development of students’ language competencies is described.